Plexiform granular cell odontogenic tumor: unicystic variant. - Siar, C.H.; Ng, K.H.; Jalil, N.A. (1991)
Plexiform granular cell odontogenic tumor of the mandible has recently been described. The cardinal histopathologic feature, as its name suggests, is a monophasic plexiform pattern of granular cells; the principal tumor in the differential diagnosis is granular cell ameloblastoma. Unlike the two previously reported cases of plexiform granular cell odontogenic tumor, which occurred as solid tumors in elderly men, the lesion reported here is a unicystic variant occurring in a middle-aged woman.